FINANCIAL STATE OF RUSSIAN REGIONS: INDIVIDUALIZATION OF THREATS - Aleksey Fyodorovich Pasynkov (Science and Innovation Center Publishing House, 2020)
The socio-economic development of Russian regions is extremely heterogeneous; at present, there is a strong differentiation of them according to various parameters. One of the main reasons for this situation is a significant gap in the regions in terms of the level of financial resources, predetermining the capabilities of regional state and local government bodies to regulate threats in the socio-economic development of territories. Under these conditions, the assessment of the financial condition of the regions and the identification of possible threats to development becomes relevant in the modern conditions of the growing crisis.